b – Coloring of Extended Duplication Graph of Dragon graph(Tn,1) and Sunlet graph(Sn) Networks - C. Shobana Sarma (Utilitas Mathematica, 2025)
The b – chromatic number ????(????), is the highest k for which G confess a b-coloring by k colors. A b-coloring of G by k colors is proper vertex k-coloring such that in each color class i there is a vertex ???????? having neighbors in every other k − 1 color classes. In this article we obtain b – chromatic number of (M[EDG(Tn,1)]) middle graph of extended duplication graph of Dragon graph, middle graph of extended duplicate graph of Sunlet graph (M[EDG(Sn)]), and total graph of (T[EDG(Tn,1)]) extended duplication graph of Dragon graph and total graph of extended duplicate graph of Sunlet graph T[EDG(Sn)].